Combination Therapies with Daclatasvir and Asunaprevir on NS3-D168 Mutated HCV in Human Hepatocyte Chimeric Mice. Issue 4 (May 2016) - Kan, Hiromi; Hiraga, Nobuhiko; Imamura, Michio; Hayes, C Nelson; Uchida, Takuro; Miyaki, Eisuke; Tsuge, Masataka; Abe, Hiromi; Aikata, Hiroshi; Miki, Daiki; Ochi, Hidenori; Ishida, Yuji; et al.
Background: Although the frequency of emergent drug-resistant strains of HCV in patients who failed to respond to simeprevir plus pegylated interferon (PEG-IFN) and ribavirin (RBV) decreased after cessation of the treatment, it is not clear whether or not the NS3-D168 variants affect the outcome of NS5A and NS3 inhibitor combination therapy. In this study, we investigated the relationship between the effect of daclatasvir plus asunaprevir treatment and the frequencies of NS3-D168 variants. Methods: HCV genotype-1b-infected human hepatocyte chimeric mice with various frequencies of NS3-D168 amino acid substitutions were treated with asunaprevir alone or in combination with daclatasvir for 4 weeks. Frequencies of NS3-D168 substitutions at baseline were analysed by ultra-deep sequencing. Some mice with NS3-D168 substitutions were treated with PEG-IFN or telaprevir for 4 weeks. Results: Mice with high frequencies of NS3-D168 showed low susceptibility to asunaprevir treatment and failed to respond to daclatasvir plus asunaprevir therapy. In contrast, mice with a low frequency (less than approximately 14%) of NS3-D168 showed a similar susceptibility to wild-type HCV-infected mice and achieved viral eradication with daclatasvir plus asunaprevir therapy. Although treatment with either telaprevir or PEG-IFN resulted in reduction of serum HCV RNA levels, no significant decrease in the frequency of NS3-D168 substitutions was achieved. Conclusions: Daclatasvir and asunaprevir treatment could eliminate NS3-D168 variant HCV if the frequency was low. It is necessary to confirm that the frequency of NS3-D168 variants has decreased sufficiently before adopting daclatasvir plus asunaprevir therapy in patients with simeprevir plus PEG-IFN/RBV treatment failure.